Enabling remote access to personal electronic medical records. - Hall, E.S (IEEE Engineering in medicine and biology magazine)
The Poket Doktor is a wireless personal healthcare system that can obtain accurate patient medical information in situations where it may not otherwise be available. The system is designed to provide a flexible, scalable method of storing and communicating critical electronic medical record information using personal handheld electronic devices. The first phase of development has succeeded in: designing the architecture for a wireless, power-efficient smart card to store and communicate medical information incorporating Bluetooth wireless technology with radiofrequency identification wakeup on the smart card to enable a fast wireless connection to a healthcare provider's device; and selecting a platform and creating application software for a handheld computing device used by healthcare providers. The Poket Doktor system assists medical personnel in obtaining accurate patient medical information in situations where it may not otherwise be available. In this manner, Poket Doktor technology will improve the quality of care delivered in emergency situations.